LONG-TERM FINANCIAL SUSTAINABILITY AND INEQUALITY OF PHARMACEUTICAL EXPENDITURE IN THE EUROPEAN UNION, 2011-2060: A COMPARATIVE ANALYSIS - Stefano Olgiati; Alessandro Danovi (European Scientific Journal, ESJ, 2014)
The European Union has achieved near-universal health coverage (Mean=99.15%; Standard Deviation=1.46%; Variation Coefficient=1%) and equity of access to healthcare services but, in the period 2000-10, such goal has been achieved at a Not Sustainable rate with total health expenditure growth (4.2%, STDDEV=2.4%) exceeding the growth rate of the GDP (1.7%,STDDEV=1.4%) by +2.5 percentage points on average and pharmaceutical expenditure (3.5%, STDDEV=3.0%) exceeding the growth rate of the GDP by +1.8 points. In the period 2011-2060 the GDP is expected to reduce and stabilize its growth rate from an average of 1.7% (STDDEV=1.4%) to an average of 1.6% with lower variation among the countries of the EU (STDDEV=0.5%). There follows that if the growth rate of health and pharmaceutical expenditure of the period 2000-10 is not reduced in the period 2011-60 only 4 nations will achieve economic and financial sustainability: Netherlands, Sweden, Denmark and Italy. Health policymakers in the European Union should account for this long-term expenditure growth pattern and reform in the efficiency and effectiveness of health and pharmaceutical care is necessary if health outcomes are to be improved and at the same time the economic and financial sustainability of the European universal welfare model is to be preserved and inequality avoided.